2021
DOI: 10.1108/itp-07-2021-0572
|View full text |Cite
|
Sign up to set email alerts
|

Digital platforms: customer satisfaction, eWOM and the moderating role of perceived technological innovativeness

Abstract: PurposeThe paper aims to investigate how customer satisfaction can be achieved in the context of digital platform services, its influence on electronic word of mouth (eWOM) and how such relationships can be moderated by perceived technological innovativeness (PTI).Design/methodology/approachThe research framework was developed and empirically tested using an online survey and analysed using structural equation modelling (SEM). Data were gathered from 501 Uber customers in London, UK.FindingsThe study recognise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 142 publications
4
12
0
Order By: Relevance
“…, 2021a). Thus, eWOM has become one of the most influential information sources for consumers' purchase decision-making (Ruiz-Alba et al. , 2021; Verma and Yadav, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2021a). Thus, eWOM has become one of the most influential information sources for consumers' purchase decision-making (Ruiz-Alba et al. , 2021; Verma and Yadav, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Consumers usually seek each other's suggestions and recommendations in the pre-purchase stage (Wang et al, 2018), as well as share their experiences and reviews in the post-purchase stage (Liu et al, 2021a). Thus, eWOM has become one of the most influential information sources for consumers' purchase decision-making (Ruiz-Alba et al, 2021;Verma and Yadav, 2021). In the digital age, eWOM occurs on various Internet platforms, such as social media, online reviews, and e-commerce websites (Ismagilova et al, 2021;Rosario et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, participation in value co-creation increases satisfaction, generating in the individual the need to transfer this satisfaction through social networks. Recently, Ruiz-Alba et al (2022) demonstrated that customer satisfaction in collaborative consumption services positively impacts eWOM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, brand preference is determined as a consumer's response to the same products and services in terms of purchase over a period of time that results in higher profits and higher market share (Carlson et al. , 2019; Prados-Pena and Del Barrio-Garcia, 2020; Ruiz-Alba et al. , 2021).…”
Section: Theoretical Background and Main Constructsmentioning
confidence: 99%